Christmas in the barn - Brown, Margaret Wise, 1910-1952 (HarperCollins, 2004)
Lyrical text relates the birth of a child in a barn among the animals, with illustrations which depict the barn and people of a present-day farm. Annotation. What child is this Who is born here Where the oxen Stomp and peer... When christmas in the barn was first published in 1952, it demonstrated all of Margaret Wise Brown's mastery at skillfully fashioning a truly childlike interpretation of the Nativity story. For this larger, full-color edition, Caldecott Honor artist Diane Goode has created a new tableau of visitors to the barn that will please generations of new readers.